An Analysis of Electric Car Advertisement Language on YouTube Platform - Sayd, Anastasia Imelda; Nazarudin, Hamzah; Seubelan, Alfiando (Journal of English Education Program, 2025)
This study investigates the language styles, functions, strategies, and imaging strategies of English-language electric car advertisements that appear on YouTube. The study adopted a qualitative descriptive method, employing data collection techniques such as recording, observation, and note-taking. Data analysis was conducted using Miles and Huberman's interactive model, integrated with Braun and Clarke"™s thematic approach. The findings reveal that electric car advertisements on YouTube employ a range of language styles to convey messages to the audience. The dominant language style is the "Hard Sell", which highlights rational and logical aspects of the product, such as energy efficiency and ease of use. Additional creative language styles include soft sell, hyperbole, metonymy, rhetorical questions, and personification. The main functions of language in these advertisements are to inform, persuade, create an image, and inspire consumer imagination regarding the electric car experience. Language strategies encompass both direct and indirect techniques designed to persuade consumers to deliver clear information and establish a positive image through emotional messaging. Electric car imaging is crafted by emphasizing a product"™s physical characteristics, quality, and advantages, focusing on cultural symbols, user personalities, and direct comparisons with competitors, thereby solidifying the product image in consumers' minds